2020
DOI: 10.1007/s10811-020-02192-3
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the foliar application of cyanobacterial hydrolysate (Arthrospira platensis) on the growth of Petunia x hybrida under salinity conditions

Abstract: Salinity is one of the environmental factors inhibiting productivity in crop plants. Available strategies to mitigate the abiotic stresses are limited. Microalgae and cyanobacteria can mitigate the adverse effects of abiotic stress due to their biostimulant properties. The aim of this work was to study the effect of hydrolysate of the ciyanobacterium Arthrospira platensis on the growth of Petunia plants under salt stress conditions over two growing seasons (winter and spring). Plants were exposed to 2.0, 2.5, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 30 publications
2
20
0
Order By: Relevance
“…In addition, the authors of [16] suggested that the advancement effect of silicon and seaweed on the flowering time might be attributed to their essential role in balancing the ratio between carbohydrates and nitrogen in favor of flowering. In accordance with our results, in [13,27] the authors showed that the positive effect of microalgae and silicon was particularly beneficial under stress conditions. A wide array of chemicals has been identified in seaweed extracts; these include polysaccharides, phenolics, fatty acids, vitamins, osmolytes, phytohormones, and hormone-like compounds involved in the plant-signaling response to abiotic stress [2].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In addition, the authors of [16] suggested that the advancement effect of silicon and seaweed on the flowering time might be attributed to their essential role in balancing the ratio between carbohydrates and nitrogen in favor of flowering. In accordance with our results, in [13,27] the authors showed that the positive effect of microalgae and silicon was particularly beneficial under stress conditions. A wide array of chemicals has been identified in seaweed extracts; these include polysaccharides, phenolics, fatty acids, vitamins, osmolytes, phytohormones, and hormone-like compounds involved in the plant-signaling response to abiotic stress [2].…”
Section: Discussionsupporting
confidence: 93%
“…Regarding ornamental plants, the authors of [9] showed that a foliar application of Arthrospira platensis improved the RDW and the number of flowers per plant. In petunias, applying microalgae stimulates bud formation in the mother plant and induces flowering in commercial petunia plants [9,27]. In our assay, the combined application of Arthrospira and silicon gave better results than using each compound alone.…”
Section: Discussionmentioning
confidence: 71%
“…Rodriguez et al [ 58 ] hypothesized a correlation between the production of gibberellin-like substances and the ability of Scytonema hofmanii extracellular products to partially counteract many of the NaCl-induced effects on growth of rice seedlings, in particular on reduction of shoot length, root dry weight, and total free porphyrin content. Bayona-Morcillo et al [ 91 ] applied an enzymatic protein hydrolysate of A. platensis , rich in cytokinins, on leaves of petunia exposed to 2.0, 2.5, and 3.0 dS m −1 EC (electrical conductivity). Increasing salinity progessively increased leaf concentration of Na + and Cl − and decreased K:Na ratio, causing deleterious effects on plant growth.…”
Section: Cyanobacterial Biostimulant Characteristics Based On the Effects On Plantsmentioning
confidence: 99%
“…However, following the application of A. platensis hydrolysate, an increase in the number of leaves, shoots, and flowers and in K:Na ratio was found in plants subjected to the highest salinity compared to the untreated controls. Aqueous extracts and hydrolysates of A. platensis have been shown to contain, in relatively high amounts, phytohormones, such as abscisic acid, cytokinins, and jasmonic acid, involved in plant response to abiotic stresses [ 91 , 128 ]. Production of abscisic acid in response to salt stress was also observed in the culture medium of Nostoc muscorum and Synechococcus leopoliensis two hours after NaCl application [ 129 ].…”
Section: Cyanobacterial Biostimulant Characteristics Based On the Effects On Plantsmentioning
confidence: 99%
“…No negative effect was observed after IC 90 treatment of the allelopathic extracts. Although it has been argued whether algae are either positively or negatively affected by crop growth [49][50][51], numerous efforts have been made to reduce algal infestation in practical agricultural fields. Because most algae rapidly reproduce and form algal blooms in hydroponic solution [52], excessively reproduced algae compete for nutrients with crops and release allelopathic toxins in certain algal species [6,52].…”
Section: Application Of Allelopathic Extracts In Hydroponic Culturementioning
confidence: 99%